Multi-crop networks for scalable, cost-effective, and impactful on-farm testing - 1000FARMS Platform (2025)
This poster showcases how the 1000FARMS platform is improving the scalability, efficiency and impact of on-farm crop variety testing by using the tricot approach in multi-crop networks. It highlights the development and validation of a tricot budgeting template to support resource planning, transparency and cost-effectiveness, and describes the engagement with national variety release committees to accept farmer-generated tricot data. The work demonstrates how coordinated, data-driven testing supports the release of farmer-preferred, climate-adapted varieties while reducing duplication and logistical costs.